ISLAMIC PERSPECTIVE DIGITAL MARKETING: BRANDING IMAGE OF COCONUT PRODUCTS TO CREATE LOYAL CUSTUMER IN SENTUL VILLAGE - Mohammad Syaiful Suib; Yulianti Yulianti (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2025)
This research discusses the implementation of digital marketing on the brand image of coconut products to create customer loyalty in Sentul Village, Gading subdistrict in increasing sales volume through e-commerce platforms. This research aims to increase digital marketing knowledge and skills in Sentul village in managing coconut production, digital marketing strategies and online sales. The research method used is descriptive qualitative. Respondents to this research include coconut farmers, village digital admins, village officials and coconut sellers in Sentul Gading village, Probolinggo Regency. The research results show that first there is a significant increase in coconut sales through digital marketing. Second: increasing people's insight and understanding regarding digital marketing, especially on social media, and also new innovations in the appearance of applications on their digital social media in the form of branding images after attending digital marketing training.